An Index of Orthognathic Functional Treatment Need (IOFTN). (June 2014) - Ireland, Anthony J; Cunningham, Susan J; Petrie, Aviva; Cobourne, Martyn T; Acharya, Priti; Sandy, Jonathan R; Hunt, Nigel P
Objective: To design a new index categorizing the functional need for orthognathic treatment. Design: Laboratory-based study. Setting: Records were obtained from two UK hospital-based orthodontic departments. Participants: A panel of four consultant orthodontists, experienced in providing orthognathic care, devised a new index of Orthognathic Functional Treatment Need (IOFTN) with the aid of the membership of the British Orthodontic Society Consultant Orthodontists Group (COG). Twenty-three consultants and post-CCST level specialists took part in the study as raters to test the validity and reliability of the new index. Methods: A total of 163 start study models of patients who had previously undergone orthognathic treatment were assessed by the panel of four consultant orthodontists using the new index (IOFTN) and the agreed category was set as the 'gold standard'. Twenty-one consultants and post-CCST level specialists then scored the models on one occasion and two scored 50 sets of models twice to determine the test–re-test reliability. Results: Kappa scores for inter-rater agreement with the expert panel for the major categories (1–5) demonstrated good to very good agreement (kappa: 0·64–0·89) for all raters. The percentage agreement ranged from 68·1 to 92% in all cases. Intra-rater agreement for the major categories was moderate to good (kappa: 0·53–0·80). Conclusions: A new index, the IOFTN, has been developed to help in the prioritization of severe malocclusions not amenable to orthodontic treatment alone. It demonstrates good content validity and good inter-rater and moderate to good intra-rater reliability. As a result of being an evolution of the IOTN, the familiar format should make it easy to determine functional treatment need within daily orthognathic practice.